Organic minerals restore the acid-base and electrolyte balance in broiler chicks with nutritionally induced metabolic acidosis - L.M. Macalintal; A.J. Pescatore; T. Ao; M.J. Ford; K.A. Dawson (Journal of Applied Animal Nutrition)
The present study evaluated the blood gas and electrolyte balance in broiler chicks fed with diets containing different levels of vitamin premix (VM) and forms of trace minerals. VM was included at 30 or 100% of commercial levels. Trace minerals were provided as either inorganic (IOM) or organic trace minerals (OTM). This experiment, which used one-day-old male broiler chicks, featured a factorial treatment structure with four treatments using 12 replicate pens (22 chicks/pen), each arranged in a randomised complete block design. An i-STAT® handheld, point-of-care, clinical analyser, loaded with blood gas, lactate and electrolyte cartridges, was used to analyse blood samples. Significant interactions for vitamin levels and mineral form were observed for bicarbonate, base excess, total carbon dioxide, ionised calcium and haematocrit levels. Using OTM, but not IOM, in the premix resulted in blood gas and electrolyte values that were comparable to those in 100% VM-fed group. The consumption of 30% VM reduced pO2 (P<0.01), sO2 (P<0.01), pH (P=0.05) and K+ with concomitant increases in lactate, glucose and Na+ (P<0.03). However, OTM tended to reverse the Na+ effect (P=0.05) along with higher partial CO2 (P<0.05). These results demonstrated the negative effects of a 30% VM diet on blood gas and electrolyte balance, which triggered nutritionally induced metabolic acidosis. However, metabolic acidosis induced by underfeeding VM (30%) was restored or normalised by using OTM, but not IOM, in the vitamin-mineral premix.